Analysis of Pregnant Women's Preparedness for Pregnancy Hazards - Silvia Saputri; Vivi Silawati; Rosmawati Lubis (Indonesian Journal of Global Health Research, 2026)
Preparedness of pregnant women in recognizing danger signs during pregnancy is a crucial factor to prevent delays in the treatment of obstetric complications. The variation in results from previous research shows the need for in-depth analysis by combining sociodemographic, individual, social, and structural-systemic factors in one analytical model. This study aims to identify the related factors and determine the most dominant variables in influencing the preparedness of pregnant women. A quantitative study with a cross-sectional design was conducted on 121 pregnant women at the Dzakirah Clinic in South Tangerang using a total sampling technique. The research instrument has gone through a validity and reliability test process; all constructs are declared valid after one item on the anxiety variable is eliminated, and show adequate internal consistency (Cronbach's Alpha ≥ 0.70). Data analysis included univariate, bivariate (correlation test), and multivariate using multiple linear regression. Bivariate analysis showed that knowledge, family support information resources, cultural norms, healthy living behaviors, pregnancy app use, anxiety, information seeking, self-efficacy, social support, perception, attitude, and involvement in health programs had a significant relationship (p<0.05). Meanwhile, parity, income, and adherence to pregnancy screenings showed no statistically significant relationship. In the final regression model, the source of pregnancy information had the highest coefficient and became the most dominant variable in influencing preparedness. Preparedness of pregnant women is more influenced by access factors and information quality than demographic characteristics.